GAMBARAN FAKTOR RESIKO PASIEN DIABETES MELITUS TIPE II Di POLIKLINIK ENDOKRIN BAGIAN/SMF FK-UNSRAT RSU Prof. Dr. R.D KANDOU MANADO PERIODE MEI 2011 - OKTOBER 2011 - Awad, Nadyah; Langi, Yuanita A.; Pandelaki, Karel (Universitas Sam Ratulangi, 2013)
Abstract: Given the high prevalence in patients with type 2 diabetes where the incidence of 650.000 new cases each year. In type-2, the pancreas does not make enough insulin to keep blood sugar levels remain normal, often because the body does not respond well to insulin. Most people do not realize had been suffering from type 2 diabetes, although the situation has become very serious. Type 2 diabetes has become a commonly experienced in the world and in Indonesia, and the numbers continue to grow due to unhealthy lifestyles, obesity and lazy to exercise. Purpose: To determine how the image of risk factors in patients with type 2 diabetes in the clinic Endocrine and Metabolic Section / SMF FK-UNSRAT BLU RSU Prof. Dr. R.D. Manado Kandou the period of May-October2011. Methods: This type of research is a descriptive study using secondary data. Population of type 2 DM patients who come for treatment at the Polyclinic Endocrine and Metabolic Section / SMF FK-UNSRAT BLU RSU Prof.Dr. R.D. Kandou Manado the period of May - October 2011. The number of samples of 138 patients comprising 60 men and 78 women. Result: The case of DM Tiipe 2 in Endocrine and Metabolic Clinic ever found in women than in men. Acquired risk factors for type 2 diabetes mellitus is a BMI> 23 ever found in an obese BMI groups 1 (25-29,9) of 37 patients, patients with stage 1 hypertension (130-159/80-99 mmHg) obtained by 80 patients , patients with dyslipidaemia as many as 22 patients, patients with a family history of as many as 45 patients, patients with age> 40 years as many as 130 patients, and patients who have risk factors for most of the patients with 3 risk factors as many as 74 patients. Conclusion: Risk factors affecting the incidence of type 2 diabetes mellitus in Endocrine and Metabolic Clinic is a BMI> 23, hypertension> 140/90 mmHg, family history,age> 40 years, dyslipidemia. Key words : Risk factors, Diabetes mellitus type 2, Endocrine and Metabolic Clinic. Â Â Abstrak: Mengingat tingginya prevalensi untuk pasien dengan DM tipe 2 dimana insidennya sebesar 650.000 kasus baru tiap tahunnya. Pada tipe-2, pankreas tidak cukup membuat insulin untuk menjaga level gula darah tetap normal, seringkali disebabkan tubuh tidak merespon dengan baik terhadap insulin tersebut. Kebanyakan orang tidak menyadari telah menderita dibetes tipe 2, walaupun keadaannya sudah menjadi sangat serius. Diabetes tipe 2 sudah menjadi umum dialami didunia maupun di Indonesia, dan angkanya terus bertambah akibat gaya hidup yang tidak sehat, kegemukan dan malas berolahraga. Tujuan: Untuk mengetahui bagaimana gambaran faktor risiko pada pasien DM tipe 2 di Poliklinik Endokrin dan Metabolik Bagian/SMF FK-UNSRAT BLU RSU Prof. Dr. R.D. Kandou Manado periode Mei - Oktober 2011. Metode: Jenis penelitian merupakan penelitian deskriptif dengan menggunakan data sekunder. Populasi pasien DM tipe 2 yang datang berobat di Poliklinik Endokrin dan Metabolik Bagian/SMF FK-UNSRAT BLU RSU Prof.Dr. R.D. Kandou Manado periode Mei-Oktober 2011. Jumlah sampel 138 pasien yang terdiri dari 60 laki-laki dan 78 perempuan. Hasil: Kasus DM Tiipe 2 di Poliklinik Endokrin dan Metabolik terbanyak didapatkan pada perempuan dibandingkan pada laki-laki. Faktor risiko yang didapatkan untuk terjadinya DM tipe 2 adalah IMT >23 terbanyak didapatkan pada IMT golongan obes 1 (25-29,9) sebanyak 37 pasien, pasien dengan hipertensi stage 1 (130-159/80-99 mmHg) didapatkan sebanyak 80 pasien, pasien dengan dislipidemia sebanyak 22 pasien, pasien dengan riwayat keluarga sebanyak 45 pasien, pasien dengan umur >40 tahun sebanyak 130 pasien, dan pasien yang memiliki faktor risiko paling banyak adalah pasien dengan tiga faktor risiko yaitu sebanyak 74 pasien. Simpulan: Faktor risiko yang berpengaruh terhadap kejadian DM tipe 2 di Poliklinik Endokrin dan Metabolik adalah IMT >23, hipertensi >140/90 mmHg, riwayat keluarga, umur > 40 tahun, dislipidemia. Kata kunci : Faktor risiko, diabetes melitus tipe 2, Poliklinik Endokrin dan Metabolik.